Clinical research Successes and pitfalls of chronic peritoneal dialysis in infants – a Polish nationwide outcome study - Jander, Anna; Makulska, Irena; Latoszyńska, Joanna; Boguszewska-Bączkowska, Hanna; Bałasz-Chmielewska, Irena; Zagożdżon, Ilona; Załuska-Leśniewska, Iga; Stefaniak, Ewa; Leszczyńska, Beata; Zachwieja, Katarzyna; Wierciński, Ryszard; Kipigroch, Hanna; et al. (Archives of Medical Science, 2010)
Introduction: Peritoneal dialysis (PD) is a preferred method of renal replacement therapy for end-stage renal disease in children. Recent advances have allowed chronic PD to be provided to children of all ages and sizes. Material and methods: The study was designed as a national (10 dialysis centres), multicentre retrospective analysis of the medical history of 33 children who started chronic peritoneal dialysis in their infancy between 1993 and 2005, with a follow-up period of at least 24 months. Results: The nutritional status of the infants was unsatisfactory. The mean SDS of body weight at the start was –2.0, at 1 year of age –1.7. Only 40% of infants were adequately nourished at 1 year of age. Long-term follow-up analysis showed that 12 children received a kidney transplant, 13 were still on dialysis (4 changed method) and 6 died (mortality rate in the first year of life of 9%). In 2 children we observed an improvement of renal function. We observed a relatively high (1/8.8 patient-months) peritonitis rate in the analysed children when compared to 1 : 22 patient-months in all children undergoing PD in Poland. Conclusions: The results of our survey have shown that the management of dialysed infants is still a challenge for the medical team and families, but long-term results of the therapy are encouraging.